Epidemiological features of flame burns in men and women with the same degree of injury - O. N. Petrovskaya; M. I. Rimzha; L. V. Zolotukhina (Military Medicine, 2026)
Research results in the epidemiology of burn injuries indicate a predominance of male victims, who tend to have deeper tissue damage. It can be assumed that this pattern is maintained at certain degrees of burns, in particular, when exposed to one of the most common thermal factors – an open flame. The main causes of these burns were the ignition of wooden materials during fires and campfires, the ignition of flammable liquids (gasoline, solvents, etc.), and household gas. The proportion of male victims with grade IIIA burns was 2.1 times higher than that of females due to more frequent contact with flammable liquids. The average age of victims increased with increasing severity of injury. Men were 1.8 times more likely to be injured while intoxicated than women. In cases of grade IV tissue damage, the relative proportion of male victims was 2.9 times higher. The average length of hospital stay increased significantly with increasing tissue damage depth and showed no statistically significant differences by gender. The overwhelming majority of adverse outcomes (88.3 %) were recorded in patients with fourth-degree burns, with equal frequency among men and women (42.9 ± 4.5 % and 36.9 ± 7.1 %; P > 0.05). Burns were sustained in 36.7 % of patients while intoxicated, with a 1.8-fold higher prevalence among men. As the severity of burn injury increased, so did the average age of the victims and the duration of hospital treatment. The majority (88.3 %) of fatalities were due to fourth-degree burns, with no significant differences in incidence between genders.